2015
DOI: 10.1007/978-3-319-25013-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrencies as a Disruption? Empirical Findings on User Adoption and Future Potential of Bitcoin and Co

Abstract: In this paper, we examine cryptocurrencies as a potentially disruptive sort of payment method. Due to its relative importance, we focus in particular on Bitcoin. Through an inductive, exploratory interview approach with 13 individuals in three distinct groups, the determinants usability, usefulness, and subjective norm that could make Bitcoin a game-changer are explored. The results reveal that most stakeholders consider perceived ease of use still rather low, with perceived usefulness varying according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 37 publications
3
68
0
Order By: Relevance
“…This finding contradicts those of Shahzad et al (2018), who reported that AW is a direct significant determinant of citizens' intention to use Bitcoin in China. In addition, the research findings reported the significance of social influence for ITU, comparable with a study by Baur et al (2015).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding contradicts those of Shahzad et al (2018), who reported that AW is a direct significant determinant of citizens' intention to use Bitcoin in China. In addition, the research findings reported the significance of social influence for ITU, comparable with a study by Baur et al (2015).…”
Section: Discussionsupporting
confidence: 83%
“…Correspondingly and related to Bitcoin, Baur et al (2015) employed an exploratory interview method, with 13 participants in three different groups. Their analysis revealed that usability, usefulness, and subjective norms are determinants of acceptance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lee (2009), the adoption of new technology is influenced by many factors including the perceived benefits, perceived risks, and ease of use. Baur, Bühler, Bick, and Bonorden (2015) found that most stakeholders perceived Bitcoin's ease of use as relatively low. Literature reviewed identified anonymity, security, costs, speculative opportunities and transaction irreversibility as the perceived benefits of adopting Bitcoin (Beer & Weber, 2015;Dupont & Squicciarini, 2015;Gao, Clark, & Lindqvist, 2016;Gentilal, Martins, & Sousa, 2017;Glaser, Zimmermann, Haferkorn, Weber, & Siering, 2014;Hur, Jeon, & Yoo, 2015;Ly, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, it is a peer‐to‐peer transaction that facilitates direct transactions between parties. Finally, it uses cryptography technology that ensures a high degree of security (Baur et al, , p. 67; Spenkelink, , p. 8).…”
Section: Introductionmentioning
confidence: 99%